2017
DOI: 10.1108/er-06-2017-0135
|View full text |Cite
|
Sign up to set email alerts
|

Trust, job satisfaction, perceived organizational performance and turnover intention

Abstract: Purpose The purpose of this paper is to examine and compare the differential impacts of job satisfaction (JS), trust (T), and perceived organizational performance (POP) on turnover intention (TI) in public and private sector organizations. Design/methodology/approach Draws on a sample of 311 employees from the service sector (129 public and 182 private) in the United Arab Emirates’ (UAE). The main concepts utilized in the study are borrowed from previous research and further tested for validity and reliabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
84
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(114 citation statements)
references
References 93 publications
9
84
0
9
Order By: Relevance
“…Scholarly studies on factors influencing consumer purchase intention or re-purchase intention from B2B E-Commerce platforms have focused on consumer perception of the vendor characteristics and quality of the relationship between the vendor, online platform, and quality of the product sold through the platform (Ganguly, Dash, & Cyr, 2009;Zeffane & Bani Melhem, 2017). Findings from these studies have either been inconclusive, biased or devoid of suitable methodology.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholarly studies on factors influencing consumer purchase intention or re-purchase intention from B2B E-Commerce platforms have focused on consumer perception of the vendor characteristics and quality of the relationship between the vendor, online platform, and quality of the product sold through the platform (Ganguly, Dash, & Cyr, 2009;Zeffane & Bani Melhem, 2017). Findings from these studies have either been inconclusive, biased or devoid of suitable methodology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Trust in the vendor means minimal perception of fraud on customers. When trust is minimal, consumers will always have a feeling of fraud especially if the vendor delays to execute the order (Zeffane & Bani Melhem, 2017). However, trust increases after the first purchase if the execution of the order was timely and the product bore the same quality as ordered by the customer(Yu Zhang et al, 2013).…”
Section: Trust In the Vendor (E-commerce Website)mentioning
confidence: 99%
“…These withdrawal cognitions emerge as a coping mechanism triggered by the unpleasant situation, in a failed endeavor to elude it. In fact, over the years, numerous studies have examined the relationship between job satisfaction and labor turnover (e.g., Allisey et al, 2014; Kim & Kao, 2014; Kuo et al, 2014; Scanlan & Still, 2013; Zeffane & Bani Melhem, 2017), concluding that satisfied employees present low or no TI. Therefore, based on these antecedents, we posit the following hypothesis:…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…However, these research were conducted in a European context. Zeffane and Melhem (2017) in their comparative study between public and private sector organisations in United Arab Emirates found that public sector employees feel that there is a greater trust between them and the public sector employer while there was a greater association between trust and turnover intention in private sector employees. Hence, it is worthwhile to examine these relationships in Asian context as well.…”
Section: Introductionmentioning
confidence: 99%